Pride and Joy - Knight, Alexander Michael (Never Say I Know, 2014)
Written as a business novel about a struggling hospital, Pride and Joy takes the reader through a journey of discovery into why good people with good intent struggle to achieve a breakthrough in performance. It offers a practical way to address the core problem of our health systems and achieve high-quality, patient-centred affordable care for all (from the author's website:www.alex-knight.com).